The abstract liberal subject, the rights holder in an exclusionary and homogeneous model - López Rojas, Carlos Mario (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
In this article I will try to demonstrate how the rights holder is historically linked to a liberal paradigm that favored the construction of a homogenous and excluding model that challenges the equal human dignity of moral agents. To the effect, the starting point is focused on the analysis of the Rawlsian subject as prototype of the citizen of the democratic-liberal societies. Such analysis, aligned with critiques of Rawls' perspective and jointly with the study of elements of rights-based justice theories, will allow us to elucidate that the rights-holder of modernity is proclaimed as universal and abstract, however, when it is embodied in juridical and political life, it becomes a particular social actor.
Keywords: democratic ideal; rights holder; modernity; liberalism; theories of justice